Treatment of Distillery Spent Wash for Irrigation Purpose by Using Sand as Adsorbent - Kumar, Bharat; Negi, Akash; Dhaliwal, Hashanpreet; Munakhia, Sparsh (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
Sand treatment of distillery effluent has great potential as a sustainable method as it is a low cost method. The aim of this investigation is to study the sand treatment method for purification of distillery spent wash. For this, the study encompassing evaluation of reduction of various physical chemical parameters (pH, COD, TS, TDS, Ca, Mg, Na and K) of distillery spent wash was checked by passing through the sand column. The distillery effluent was acidic (pH 4.7) and dark brown in color which often cause psychological fear in farmers for utilization. Sand treatment of spent wash exhibited good reduction in COD, TS, TDS, Mg, Na, Ca, after 72 hour treatment and increase in pH toward pH 7. Treated spent wash showed a good growth of wheat seeds.